Do defense expenditures augment economic growth in Pakistan and India? A Deger-type analysis using GMM approach - Muhammad Ramzan Sheikh; Imran Sharif Chaudhry (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
Defense spending is a multifaceted phenomenon. In recent years, economists and policy makers have been interested in the explanation of the relationship between defense spending and macroeconomic variables especially growth. This study explores the connection between defense outlays and growth in two neighboring but hostile countries i.e. Pakistan and India by applying GMM technique to Deger-type model. The findings of study for Pakistan reveal that the net effect of defense spending is positive while for India it turns out to be negative. It means that the defense sector in Pakistan fosters the economic growth via aggregate demand and modernization effects. For India, defense sector is hampering growth due to reallocation of resources and creation of new resources arguments.
Keywords: 330; defense expenditures; economic growth; deger-type analysis; GMM approach